A comparative study on prognostic relevance of various severity scoring systems of acute pancreatitis in present day surgical practice - Shamita, C; Arghya, B; Soumika, B (Department of Surgery, UKM Medical Centre, 2012)
Prior assessment of severity is very important in the management of acute pancreatitis. The purpose of our study is to compare the predictive efficacy of various severity scoring systems for acute pancreatitis. This study was conducted in patients admitted with acute pancreatitis in Medical College Kolkata, between January 2011 to November 2011 by doing a prospective analysis of patients’ case notes. There was no significant difference in median APACHE II score on admission and after 48 hours in our study. Ranson’s and APACHE II score was found to have similar sensitivity and negative likelihood ratio. Ranson’s and CTSI had similar PPV and PLR. Ranson’s score proved equal to the APACHE II score for predicting mortality and the development of organ dysfunction. The LR+ of MGMOF score (cut off at ≥2) after 48 hours, MGMOF score (cut off at ≥2) on admission, MGMOF score >0 after 48 hours and on admission and Ranson’s were almost comparable. All the scores under study except Goris MOF at a cut off ≥2 on admission had good predictive value in terms of different predictive accuracy parameters. CTSI and Ranson’s score can be most useful to identify mild pancreatitis cases but can also be useful in severe pancreatitis patients to some extent. However, Ranson’s score can not be applied for prediction of severity after 48 hours.